Optimalisasi Kegiatan KWT dalam Pembuatan Pupuk Organik Sebagai Solusi Peningkatan Kesejahteraan Petani di Desa Wates - Septrianto, Wahyu; Ariaputra, Rafif Fathin; Alanuari, M.; Nurrahman, Daffa; Hidayat, Tsabitul; Sasongko, Yogi Banar (Abdimas Indonesian Journal, 2025)
The Community Service Program activities carried out in Wates Village focused on empowering Women Farmers Groups (KWT) in the production of organic fertilizers as a solution to improve the welfare of farmers and support sustainable agriculture. The program involved training in the production of organic fertilizers using local materials, such as livestock manure and plant residues, which are easily found around the village. This training has successfully improved the skills of KWT members in producing organic fertilizers using efficient techniques. The use of organic fertilizers has shown a significant improvement in soil quality, plant resistance to pests and diseases, and agricultural productivity. In addition, this activity also helps reduce dependence on chemical fertilizers, which contributes to reducing production costs and negative environmental impacts. Thus, this program contributes to the achievement of more environmentally friendly and sustainable agriculture, and improves the economic welfare of KWT members in Wates Village.